The origin of continental carbonates in Andean salars: A multi-tracer geochemical approach in Laguna Pastos Grandes (Bolivia). (15th June 2020) - Muller, E.; Gaucher, E.C.; Durlet, C.; Moquet, J.S.; Moreira, M.; Rouchon, V.; Louvat, P.; Bardoux, G.; Noirez, S.; Bougeault, C.; Vennin, E.; Gérard, E.; et al.
Abstract: In continental volcanic settings, abundant carbonate precipitation can occur with atypical facies compared to marine settings. The (bio-)chemical processes responsible for their development and early diagenesis are typically complex and not fully understood. In the Bolivian Altiplano, Laguna Pastos Grandes hosts a 40-km 2 carbonate platform with a great diversity of facies and provides an ideal natural laboratory to understand the processes responsible for the precipitation of carbonates in a continental province dominated by volcanism. In order to trace the origin of both water and solutes in the lagoon, the major element and stable isotope compositions (δ 2 H-δ 18 O, δ 37 Cl, δ 7 Li, δ 11 B and 87 Sr/ 86 Sr) of the spring and stream waters were characterized, as well as the stable isotope compositions (δ 13 C, δ 15 N) and noble gas isotope ratios of hydrothermal gases associated with spring waters. The results show that thermal springs discharging on the carbonate platform are close to saturation with calcite. PHREEQC modeling, together with fluid geochemistry and temperature estimated from a combination of geothermometers, indicate that Ca in these springs is inherited from the alteration of the volcanic bedrock by aqueous fluids heated at ∼225 °C and enriched in magmatic mantle-derived CO2 . Our results clearly show that the main driver for the precipitation of modern carbonates in Laguna Pastos Grandes is the deeply sourced CO2, which boosts the alteration of volcanic rocks at depth.